To find new markers for poor recovery of inflammatory bowel disease based on intestinal barrier function and inflammatory stress response markers - Lin, Renjing; Yang, Zongliang (Journal of Medical Biochemistry, 2026)
Objective: Inflammatory bowel disease (IBD) is one of the common diseases in the department of gastroenterology. We conducted a cross-sectional study on 74 cases of IBD admitted to our hospital from January 2024 to April 2025, with a focus on the changes of serum cytokines in the patients. Subsequently, based on these cytokines, we developed a novel risk model for poor recovery in IBD.Methods: Based on the estimation of sample size and the screening of inclusion and exclusion criteria, we included 74 IBD patients as the research subjects (January 2024 to April 2025) for a cross-sectional survey. Key indicators were measured, including intestinal barrier markers (I-FABP, DAO, FC), inflammatory cytokines (IL-6, TNF-α, IL-10), Th17/Treg ratio, and stress hormones (Cor, ACTH). Subsequently, Logistic regression analysis was used to establish a risk model for predicting poor recovery of patients.Results: Patients with IBD have obvious intestinal barrier function impairment: intestinal barrier integrity makers—I-FABP, DAO, and FC—declined by 31.42%, 45.11%, and 37.31%, respectively (P